Namibia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Namibia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic has sharply deteriorated Namibia's short-term macroeconomic outlook, giving rise to urgent balance of payments (BOP) and fiscal financing needs. After an initial outbreak peaked in August, a second wave hit in late 2020. Containment measures have negatively impacted domestic consumption and economic activity, weighing on tax revenues collection. Furthermore, worsening global conditions have hindered mining production and exports, tourism receipts, and investment inflows. The economy is expected to have sharply contracted by 7.2 percent in 2020, and the recovery is set to remain subdued in 2021.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Namibia